Electrochemical Advanced Oxidation Processes Using Diamond Technology: A Critical Review - Brosler, Priscilla; Girão, Ana V.; Silva, Rui F.; Tedim, João; Oliveira, Filipe J. (Environments (Basel, Switzerland), 2023)
Re-evaluation of conventional wastewater treatment processes is of paramount importance to improve the overall quality of our aquatic environment. Electrochemical Advanced Oxidation Processes (EAOPs) are the most promising alternative methods with application in wastewater treatment facilities since in situ electrogenerated oxidant agents degrade and mineralize a wide range of water pollutants. Boron-doped diamond (BDD) technology has proven its excellency in the anodic oxidation (AO) of different pollutants. In this work, we describe the use of a systematic literature review (SLR) methodology and a bibliometric analysis tool for the assessment of a representative sample of work (hundreds of publications) concerning the synergism between AO using BDD technology and other oxidation methods. One section of the discussion relates to different techniques used to enhance the AO performance of BDD technology, namely persulfate radicals or ozone and photoelectrocatalysis, whereas the second one considers Fenton-based reactions. A standard synergism effect occurs between AO using BDD technology and the add-ons or the Fenton-based methods, resulting in the enhancement of the degradation and mineralization efficiencies. The future of EAOPs using BDD technology must include renewable energy sources to self-sustain the overall process, and further research on the subject is mandatory to enable the effective acceptance and application of such processes in wastewater remediation facilities.